Study of new pathogenetic mechanisms of diabetic retinopathy development in patients with diabetic foot syndrome - Kryzhevskyi, Yevhenii; Bilyayeva, Olga; Rykov, Sergiy; Shargorodska, Iryna; Osadchaya, Oksana; Barinov, Yurii; Petrovsky, Mykola (Journal of Education, Health and Sport, 2021)
Introduction and purpose. Diabetes is one of the underlying causes of blindness and other long-term negative consequences that significantly affect patients’ quality of life. The study aimed to determine the indicators characterizing the pathogenetic mechanisms of the development of vascular dysfunction, in particular diabetic retinopathy (DR), and the relationship of these changes with nitric oxide. Material and methods. There were 2114 patients with various surgical diseases under observation (including 1073 patients with purulent-septic soft tissue diseases), among them there were 193 patients with type 2 diabetes mellitus (DM) and 134 patients with Wagner stage 2-5 diabetic foot syndrome (DFS) and diabetic retinopathy in the main group (268 eyes). The comparison group included 59 patients (118 eyes) of the corresponding age with DM without DFS and DR. Both groups were the same in age and gender. Results. The level of the end products of nitric oxide metabolism in peripheral blood was found to be 1.78 times (p<0.01) higher compared with patients without DR. A decrease in the activity of superoxide dismutase (SOD) in patients with DR was by 1.56 times (p<0.01) lower relative to the comparison group. The content of thiobarbituric acid (TBA)-active products in the peripheral blood of patients of the main group exceeded by 1.58 times (p <0.01) the reference values of patients without DR. When determining the content of S-nitrosithiols, an increase in these indicators in the main group was found to be 2.38 times (p<0.01). Patients in the main group with DR also showed a 5.13-fold (p<0.001) increase in peripheral blood homocysteine concentration. NO is known to have both positive and harmful effects depending on its concentration. On the one hand, NO causes relaxation of blood vessels by reducing blood pressure, prevents platelet aggregation and adhesion, limits LDL cholesterol oxidation, suppresses smooth muscle cell proliferation, and reduces the expression of proinflammatory genes that are associated with atherogenesis. It is known that NO can have both positive and harmful effects, depending on its concentration. On the one hand, NO causes relaxation of blood vessels, reducing blood pressure, prevents platelet aggregation and adhesion, limits the oxidation of LDL cholesterol, suppresses the proliferation of smooth muscle cells, and reduces the expression of pro-inflammatory genes that are associated with atherogenesis. On the other hand, NO interacts with O2-, leading to the inactivation of NO and the production of peroxynitrite, which post-transcriptionally modifies proteins and negatively affects their function. This can contribute to endothelial dysfunction by stimulating the production of inflammatory mediators and lipid peroxidation and thus increasing cell permeability. Conclusions. The findings show that the patients with diabetes mellitus complicated by retinopathy and DFS had a significant increase in the content of nitric oxide in the peripheral blood, the cause of which is hyperglycemia. The use of an intercellular mediator (nitric oxide), which contributes to the physiological regulation of the hemodynamics of the eye, protects vascular endothelial cells from pathogenic factors of ischemia, will help clinicians choose an effective pharmacological therapy appropriate for a particular patient and a particular eye.